Preparation of cellulose-based ion conductive gel electrolyte and application thereof in self-driven information display device

CN122672249APending Publication Date: 2026-09-01SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610653957.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-13
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提出一种纤维素基离子导电凝胶电解质的制备及其在自驱动信息显示器件中的应用,以解决现有电解质体系在柔性信息显示器件中存在的结构稳定性不足、低温环境适应性较差以及离子传输性能受限等问题

Benefits of technology

本发明提供一种纤维素基离子导电凝胶电解质,采用离子液体对纤维素原料进行溶解,并结合聚乙烯醇构建凝胶体系,有利于形成均匀稳定的凝胶结构;其中,纤维素组分能够提供基础支撑网络,聚乙烯醇能够改善凝胶体系的成膜性与柔韧性,从而使所得凝胶电解质具备良好的结构完整性。通过引入丙烯酰胺构建复合凝胶结构,使凝胶内部形成更加稳定的网络体系;同时结合离子导电组分处理,使离子能够在凝胶内部形成连续传输路径,从而满足信息显示器件对离子传输过程的基本需求。采用高氯酸锂作为离子导电组分,并结合乙二醇对凝胶体系进行处理,有利于维持凝胶内部离子传输环境的稳定性,使所制备的凝胶电解质能够应用于自供能信息显示器件中,实现可逆的电化学响应与可视化颜色变化。所制备的纤维素基离子导电凝胶电解质具有良好的柔性与界面适配性,可与柔性导电电极及基底形成稳定接触,在器件弯折或形变过程中仍能够保持基本结构稳定,从而满足柔性信息显示器件的使用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122672249A_ABST
    Figure CN122672249A_ABST
Patent Text Reader

Abstract

This invention discloses the preparation of a cellulose-based ion-conductive gel electrolyte and its application in a self-powered information display device. A precursor is formed by dissolving cellulose in an ionic liquid and cross-linking it. This precursor is then polymerized in situ to construct a composite gel structure, followed by treatment with ion-conductive components to obtain a gel electrolyte with ion-conducting capabilities. The gel electrolyte serves as the ion-conducting layer, which, together with a patterned conductive polymer electrode layer, a metal thin film layer, and an encapsulation layer, constitutes the self-powered information display device. The device utilizes a micro-voltage generated by pressing to drive an internal electrochemical process, initiating ion migration and reversible redox reactions in the electrode materials, thereby achieving a visual information display response. This addresses the problems of poor structural stability, weak low-temperature adaptability, and limited ion transport inherent in existing electrolytes in flexible information display devices. By constructing a gel electrolyte system with stable structure and excellent ion conductivity, the device's operational stability and environmental adaptability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor technology, specifically relating to the preparation of a cellulose-based ion-conductive gel electrolyte and its application in self-driven information display devices. Background Technology

[0002] With the rapid development of flexible electronics technology and the smart packaging industry, paper-based information labels with visual display functions have been widely used in anti-counterfeiting, traceability, and information identification. These labels typically achieve dynamic information display based on the color-changing effect of materials under external stimuli (such as electric fields, light, etc.).

[0003] Currently, liquid electrolytes are commonly used as ion transport media in information display devices to achieve high ion conduction efficiency. While these systems exhibit good electrochemical response performance, their high fluidity leads to issues such as easy leakage, stringent packaging requirements, and insufficient long-term stability, limiting their application in flexible or deformable devices. Another type of system uses gel electrolytes instead of traditional liquid electrolytes. By introducing ion-conducting components into a polymer network, the system simultaneously possesses a certain degree of mechanical stability and ion transport capability. This type of electrolyte improves the structural stability of devices to some extent, but in practical applications, it still suffers from performance degradation at low temperatures, limited ion transport capability, and insufficient overall environmental adaptability.

[0004] Building upon the aforementioned systems, some studies have employed natural polymers to construct gel electrolyte systems, aiming to improve the environmental friendliness and structural stability of these materials. Cellulose, due to its wide availability and excellent film-forming properties, has been used to construct gel electrolyte network structures. However, existing cellulose-based electrolyte systems still have limitations in ion transport efficiency and low-temperature stability, and their practical application performance in information display devices requires further improvement. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, the present invention aims to propose a method for preparing a cellulose-based ion-conductive gel electrolyte and its application in self-driven information display devices. This addresses the problems of insufficient structural stability, poor low-temperature adaptability, and limited ion transport performance of existing electrolyte systems in flexible information display devices. Furthermore, by constructing a gel electrolyte system with a stable structure and good ion conductivity, the overall operational stability and environmental adaptability of the information display device are improved.

[0006] The technical solution adopted in this invention is: In a first aspect, the present invention provides a method for preparing a cellulose-based ion-conducting gel electrolyte, comprising the following steps: S1. Melt 1-allyl-3-methylimidazolium chloride at 80-90℃, and add 1%~3% bamboo dissolving pulp, 8-12% dimethyl sulfoxide and 3-5% polyvinyl alcohol by mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a homogeneous and transparent solution is formed. Cool down to 50-60℃, add 8-10% epichlorohydrin by mass of bamboo dissolving pulp and stir evenly. Pour into a polytetrafluoroethylene mold to form, and then place in deionized water for regeneration to obtain the gel precursor. S2. Weigh acrylamide and dissolve it in deionized water at 2%-10% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution until it swells completely, and then carry out in-situ polymerization at 40-70℃ to obtain a composite gel. S3. Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 0.8-1.2 mol / L, and ethylene glycol accounts for 15-25% of the final solution volume. Immerse the composite gel in the lithium perchlorate mixed solution until it swells completely. After removing it, wipe off the surface moisture to obtain the cellulose-based ion-conductive gel electrolyte.

[0007] Secondly, the present invention provides a self-driven information display device comprising a cellulose-based ion-conductive gel electrolyte as described in the first aspect, comprising a flexible substrate, on which conductive polymer ink with display characteristics is sequentially superimposed and printed using a flexographic printing process; a base layer is formed by coating with a solid block photosensitive resin plate; and a patterned surface layer is formed by overprinting with a patterned photosensitive resin plate. The two together constitute a patterned conductive polymer electrode layer, and the patterned surface layer defines the active area that serves as the display portion; an encapsulation frame is provided circumferentially on the display portion of the patterned conductive polymer electrode layer, defining a square receiving cavity, within which a non-triggering area and a triggering space area are provided; the cellulose-based ion-conductive gel electrolyte is attached to the surface of the patterned conductive polymer electrode layer, covering the non-triggering area and part of the triggering space area, forming an ion-conducting layer; a metal foil is covered on the surface of the patterned conductive polymer electrode layer, completely covering the triggering space area, forming a metal thin film layer; a polyethylene terephthalate film is covered on top of the ion-conducting layer and the metal thin film layer to form an encapsulation layer, ultimately forming a self-driven information display device; When a trigger operation is applied to the position corresponding to the trigger space area on the top of the self-driven information display device, the encapsulation layer undergoes local deformation, driving the metal thin film layer downward to contact the patterned conductive polymer electrode layer, thereby forming an instantaneous conductive path in this area, and generating a self-generated potential inside the device. At this time, the metal thin film layer acts as an electron supply terminal, establishing an electrical connection with the patterned conductive polymer electrode layer. Under the action of the ion conduction layer, ions undergo directional migration inside the device and participate in the reversible redox reaction at the electrode interface, causing the patterned conductive polymer electrode layer to undergo a redox reaction, thereby causing a change in the visual color and realizing the rapid display of patterned information.

[0008] Furthermore, the preparation process of the conductive polymer ink with display properties is as follows: Take poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add 3% to 5% dimethyl sulfoxide (DMSO), 3% to 10% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) according to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 hours, and then sonicate for 30 minutes to disperse evenly.

[0009] Thirdly, the present invention provides a method for preparing a self-driving information display device, comprising the following steps: Step 1: Cut the flexible substrate and remove surface dust and impurities through a dust removal process; design solid blocks and photosensitive resin plates with patterns according to the design dimensions; Step 2: Perform ultrasonic cleaning on the polyethylene terephthalate film; Step 3: Prepare conductive polymer ink with display properties for patterning conductive polymer electrode layers. On a flexible substrate, use flexographic printing to sequentially print the conductive polymer ink with display properties. First, use a solid photosensitive resin plate for coating and printing. After single printing and drying, multi-layer overprinting and curing are performed to obtain a base layer. Pure formic acid is drop-coated onto the surface of the base layer and air-dried at room temperature. Then, use a patterned photosensitive resin plate to overprint and form a patterned surface layer. After drying, the patterned conductive polymer electrode layer is finally obtained. Step 4: Attach a 0.5-1mm thick encapsulation frame to the circumferential part of the patterned conductive polymer electrode layer to form a square receiving cavity. The square receiving cavity contains a non-trigger area and a trigger space area. Step 5: Attach the prepared cellulose-based ion-conducting gel electrolyte to the surface of the patterned conductive polymer electrode layer, covering the non-trigger area and part of the trigger space area to form an ion-conducting layer; cover the surface of the patterned conductive polymer electrode layer with a metal foil with a thickness lower than the encapsulation border, completely covering the trigger space area to form a metal thin film layer; cover the ion-conducting layer and the metal thin film layer with a polyethylene terephthalate film to form an encapsulation layer, finally forming a self-driven information display device.

[0010] Furthermore, the flexible substrate mentioned in step 1 is digital proofing paper, and the metal foil is zinc foil, aluminum foil, or iron foil with a thickness of 0.1~0.5mm.

[0011] Furthermore, the ultrasonic cleaning process in step 2 is as follows: first, the surface of the polyethylene terephthalate film is wiped with detergent, then the polyethylene terephthalate film is ultrasonically cleaned for 5 minutes each with deionized water and anhydrous ethanol, and finally dried by nitrogen purging.

[0012] Furthermore, the flexographic printing described in step 3 adopts the following process parameters: the squeegee angle is fixed at 60°, the squeegee loading pressure is 6-7N, the printing pressure is 100-250N, the printing speed is 0.2m / s-0.6m / s, and an anilox roller with a line count of 110 l / cm and an ink load of 14mL / m² is used.

[0013] Furthermore, the drying process described in step 3 involves placing the food in an oven at 105°C for 30 minutes to dry at a constant temperature.

[0014] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a cellulose-based ion-conductive gel electrolyte. Cellulose raw materials are dissolved using an ionic liquid, and a gel system is constructed using polyvinyl alcohol, which facilitates the formation of a uniform and stable gel structure. The cellulose component provides a basic supporting network, while polyvinyl alcohol improves the film-forming properties and flexibility of the gel system, resulting in a gel electrolyte with good structural integrity. The introduction of acrylamide to construct a composite gel structure creates a more stable network system within the gel. Simultaneously, treatment with ion-conductive components allows ions to form continuous transport paths within the gel, meeting the basic requirements of information display devices for ion transport. Using lithium perchlorate as the ion-conductive component, combined with ethylene glycol treatment of the gel system, helps maintain the stability of the ion transport environment within the gel, enabling the prepared gel electrolyte to be used in self-powered information display devices, achieving reversible electrochemical responses and visualized color changes. The prepared cellulose-based ion-conductive gel electrolyte exhibits good flexibility and interfacial compatibility, forming stable contact with flexible conductive electrodes and substrates. It maintains basic structural stability even during device bending or deformation, thus meeting the requirements of flexible information display devices.

[0015] This invention constructs a patterned conductive polymer electrode layer and an ion-conducting layer on a flexible substrate. A circumferential encapsulation frame is provided on the display portion of the patterned conductive polymer electrode layer, defining a square cavity. Within the square cavity, a non-triggering region and a triggering space region are defined. The ion-conducting layer is attached to the surface of the patterned conductive polymer electrode layer, covering the non-triggering region and part of the triggering space region. A metal thin film layer completely covers the triggering space region. A gel electrolyte is used as the ion-conducting layer, which, together with the patterned conductive polymer electrode layer, the metal thin film layer, and the encapsulation layer, constitutes a self-driving information display device. In the default state, the patterned conductive polymer electrode layer and the metal thin film layer are in a potential equilibrium state, and no effective electrochemical driving force is formed inside the device. At this time, the ions in the ion-conducting layer are uniformly distributed, and the overall system does not undergo any visible color change; the self-driving information display device maintains its initial state. When a trigger operation is applied to the position corresponding to the trigger space region on the top of the device, contact conduction occurs in the internal structure, generating a self-generated potential within the device. Driven by the ion-conducting layer, ions migrate directionally within the device and participate in the reversible redox reaction at the electrode interface. This causes an electrochemical redox reaction process in the conductive polymer electrode layer, resulting in changes in its optical properties and achieving a visible electrochromic response. Simultaneously, due to the excellent spatial continuity and interfacial compatibility of the ion-conducting gel electrolyte, the device can maintain basic ion transport channels even under bending or deformation conditions, thus ensuring the stability and consistency of the electrochromic response. Attached Figure Description

[0016] Figure 1This is a structural diagram of an information display device; Figure 2 A top view of the information display device; Figure 3 is a schematic diagram of the flexible photosensitive resin plate structure, wherein Figure 3(a) is a solid block flexible photosensitive resin plate; and Figure 3(b) is a patterned flexible photosensitive resin plate. Figure 4 This is a schematic diagram illustrating the changes in the display state of the information display device before and after triggering.

[0017] In the figure: 1-flexible substrate; 2-patterned conductive polymer electrode layer; 3-ion conduction layer; 4-metal thin film layer; 5-encapsulation layer. Detailed Implementation

[0018] The structural and working principles of the present invention will be further described in detail below with reference to the accompanying drawings.

[0019] like Figure 1 , 2 As shown, a trigger-activated paper-based visual information response label includes a flexible substrate 1. A patterned conductive polymer electrode layer 2 is formed by sequentially printing conductive polymer ink with display properties onto the flexible substrate 1 using a flexographic printing process. A base layer is formed by coating with a solid block photosensitive resin plate as shown in Figure 3(a), and then a patterned surface layer is formed by overprinting with a patterned photosensitive resin plate as shown in Figure 3(b). The patterned surface layer defines the active area that serves as the display portion. A packaging frame is circumferentially arranged around the display portion of the patterned conductive polymer electrode layer 2, defining a square receiving cavity. A non-triggering area and a triggering space area are arranged within the square receiving cavity. A pre-prepared cellulose-based ion-conductive gel electrolyte is attached to the surface of the patterned conductive polymer electrode layer 2, covering the non-triggering area and part of the triggering space area, forming an ion-conducting layer 3. A metal foil is then covered on the surface of the patterned conductive polymer electrode layer 2, completely covering the triggering space area, forming a metal thin film layer 4. The thickness of the metal foil is lower than the packaging frame, and the metal foil is selected as zinc foil, aluminum foil, or iron foil with a thickness of 0.1~0.5 mm. A polyethylene terephthalate film is deposited over the ion-conducting layer 3 and the metal thin film layer 4 to form an encapsulation layer 5, ultimately forming a flexible self-driving information display device, as shown in the structure. Figure 4 As shown.

[0020] When there is no external triggering, the conductive polymer electrode layer 2 and the counter electrode layer 4 are in a potential equilibrium state, and no effective electrochemical driving force is formed inside the device. At this time, the ions in the ion conduction layer 3 are in a uniform distribution state, and the overall system does not undergo visible color change. The self-driven information display device maintains its initial state.

[0021] When external mechanical pressure is applied to the trigger space area of ​​the self-driven information display device, the encapsulation layer 5 undergoes local deformation, driving the metal thin film layer 4 downward to contact the patterned conductive polymer electrode layer 2, thereby forming a momentary conductive path in this area, and generating a self-generated potential inside the device. At this time, the metal thin film layer 4 acts as an electron supply terminal, establishing an electrical connection with the patterned conductive polymer electrode layer 2. Under the action of the ion-conducting layer 3, ions undergo directional migration inside the device and participate in the reversible redox reaction at the electrode interface, causing the patterned conductive polymer electrode layer 2 to undergo a redox reaction, thereby causing a change in its optical properties and realizing a visualized electrochromic response. Due to the good spatial continuity and interface adaptability of the ion-conducting gel electrolyte 3, the device can still maintain a basic ion transport channel under bending or deformation conditions, thus ensuring the stability and consistency of the electrochromic response. At the same time, in the non-trigger area, since no structural contact occurs, the metal thin film layer 4 and the corresponding electrode area remain separated, the conductive path is not established, the electrochromic reaction cannot occur, and thus the original state is maintained without color change. This enables selective response between triggered and non-triggered areas, ensuring clear boundaries for pattern display.

[0022] Example 1: A method for fabricating a self-driving information display device, comprising the following steps: Step 1: Select digital proofing paper as flexible substrate 1 for cutting, and remove surface dust and impurities through dust removal treatment; according to the design size, design solid blocks and photosensitive resin plates containing patterns; Step 2: First, wipe the surface of the polyethylene terephthalate film with dish soap, then use deionized water and anhydrous ethanol to ultrasonically clean the polyethylene terephthalate film for 5 minutes each, and finally blow it dry with nitrogen. Step 3: Prepare a conductive polymer ink with display properties for patterning the conductive polymer electrode layer 2: Take a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add, in sequence, 5% dimethyl sulfoxide (DMSO), 3% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) relative to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 h, and then sonicate for 30 min to disperse evenly; On a flexible substrate 1, conductive polymer inks with display properties are sequentially printed using a flexographic printing process. The squeegee angle is 60°, the squeegee loading pressure is 6N, the printing pressure is 150N, the printing speed is 0.3m / s, and an anilox roller with a line count of 110 l / cm and an ink load of 14mL / m² is used. First, a solid photosensitive resin plate is used for coating and printing. After a single printing, the ink is dried in an oven at 105℃ for 30 minutes. After multi-layer overprinting and curing, a base layer is obtained. Pure formic acid is drop-coated onto the surface of the base layer and air-dried at room temperature. Then, a patterned photosensitive resin plate is used for overprinting to form a patterned surface layer. After drying in an oven at 105℃ for 30 minutes, the patterned conductive polymer electrode layer 2 is finally prepared. Step 4: A 0.5mm thick encapsulation frame is attached circumferentially to the display portion of the patterned conductive polymer electrode layer 2 to form a square receiving cavity. The square receiving cavity contains a non-trigger area and a trigger space area. Step 5: Preparation of cellulose-based ion-conducting gel electrolyte: (1) Melt 1-allyl-3-methylimidazolium chloride at 90°C, and add 1% bamboo dissolving pulp, 10% dimethyl sulfoxide and 4% polyvinyl alcohol according to its mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a uniform transparent solution is formed. Cool down to 60°C, add 10% epichlorohydrin by mass of bamboo dissolving pulp, stir for 5 min, pour into a polytetrafluoroethylene mold, let stand at 4°C for 24 h to form, and then place in deionized water to regenerate to obtain the gel precursor. (2) Weigh acrylamide and dissolve it in deionized water at 2% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution for 24 hours to fully swell, and then perform in-situ polymerization at 60°C to obtain a composite gel. (3) Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 1 mol / L, and ethylene glycol accounts for 20% of the final solution volume. Soak the composite gel in the lithium perchlorate mixed solution for 24 hours to fully swell. After taking it out, wipe off the surface moisture to obtain cellulose-based ion-conductive gel electrolyte.

[0023] A cellulose-based ion-conducting gel electrolyte is attached to the surface of a patterned conductive polymer electrode layer 2, covering the non-trigger area and part of the trigger space area to form an ion-conducting layer 3. A metal foil with a thickness lower than the encapsulation border is covered on the surface of the patterned conductive polymer electrode layer 2, completely covering the trigger space area to form a metal thin film layer 4. A polyethylene terephthalate film is then covered on top of the ion-conducting layer 3 and the metal thin film layer 4 to form an encapsulation layer 5, ultimately forming a flexible self-driving information display device.

[0024] Example 2: A method for fabricating a self-driving information display device, comprising the following steps: Step 1: Select digital proofing paper as flexible substrate 1 for cutting, and remove surface dust and impurities through dust removal treatment; according to the design size, design solid blocks and photosensitive resin plates containing patterns; Step 2: First, wipe the surface of the polyethylene terephthalate film with dish soap, then use deionized water and anhydrous ethanol to ultrasonically clean the polyethylene terephthalate film for 5 minutes each, and finally blow it dry with nitrogen. Step 3: Prepare a conductive polymer ink with display properties for patterning the conductive polymer electrode layer 2: Take a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add, in sequence, 3% dimethyl sulfoxide (DMSO), 10% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) relative to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 hours, and then sonicate for 30 minutes to disperse evenly; On a flexible substrate 1, conductive polymer inks with display properties are sequentially printed using a flexographic printing process. The squeegee angle is 60°, the squeegee loading pressure is 7N, the printing pressure is 200N, the printing speed is 0.4m / s, and an anilox roller with a line count of 110 l / cm and an ink loading of 14mL / m² is used. First, a solid photosensitive resin plate is used for coating and printing. After a single printing, the ink is dried in an oven at 105℃ for 30 minutes. After multi-layer overprinting and curing, a base layer is obtained. Pure formic acid is drop-coated onto the surface of the base layer and air-dried at room temperature. Then, a patterned photosensitive resin plate is used for overprinting to form a patterned surface layer. After drying in an oven at 105℃ for 30 minutes, the patterned conductive polymer electrode layer 2 is finally prepared. Step 4: A 0.7mm thick encapsulation frame is attached circumferentially to the display portion of the patterned conductive polymer electrode layer 2 to form a square receiving cavity. The square receiving cavity contains a non-trigger area and a trigger space area. Step 5: Preparation of cellulose-based ion-conducting gel electrolyte: (1) Melt 1-allyl-3-methylimidazolium chloride at 80°C, and add 3% bamboo dissolving pulp, 12% dimethyl sulfoxide and 3% polyvinyl alcohol according to its mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a uniform transparent solution is formed. Cool down to 50°C, add epichlorohydrin at 8% of the mass of bamboo dissolving pulp, stir for 5 min, pour into a polytetrafluoroethylene mold, let stand at 4°C for 24 h to form, and then place in deionized water to regenerate to obtain the gel precursor. (2) Weigh acrylamide and dissolve it in deionized water at 4% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution for 24 hours to fully swell, and then perform in-situ polymerization at 70°C to obtain a composite gel. (3) Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 0.8 mol / L, and ethylene glycol accounts for 25% of the final solution volume. Soak the composite gel in the lithium perchlorate mixed solution for 24 hours to fully swell. After taking it out, wipe off the surface moisture to obtain cellulose-based ion-conductive gel electrolyte.

[0025] A cellulose-based ion-conducting gel electrolyte is attached to the surface of a patterned conductive polymer electrode layer 2, covering the non-trigger area and part of the trigger space area to form an ion-conducting layer 3. A metal foil with a thickness lower than the encapsulation border is covered on the surface of the patterned conductive polymer electrode layer 2, completely covering the trigger space area to form a metal thin film layer 4. A polyethylene terephthalate film is then covered on top of the ion-conducting layer 3 and the metal thin film layer 4 to form an encapsulation layer 5, ultimately forming a flexible self-driving information display device.

[0026] Example 3: A method for fabricating a self-driving information display device, comprising the following steps: Step 1: Select digital proofing paper as flexible substrate 1 for cutting, and remove surface dust and impurities through dust removal treatment; according to the design size, design solid blocks and photosensitive resin plates containing patterns; Step 2: First, wipe the surface of the polyethylene terephthalate film with dish soap, then use deionized water and anhydrous ethanol to ultrasonically clean the polyethylene terephthalate film for 5 minutes each, and finally blow it dry with nitrogen. Step 3: Prepare a conductive polymer ink with display properties for patterning the conductive polymer electrode layer 2: Take a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add, in sequence, 3% dimethyl sulfoxide (DMSO), 5% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) relative to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 hours, and then sonicate for 30 minutes to disperse evenly; On a flexible substrate 1, conductive polymer inks with display properties are sequentially printed using a flexographic printing process. The squeegee angle is 60°, the squeegee loading pressure is 6.5N, the printing pressure is 250N, the printing speed is 0.6m / s, and an anilox roller with a line count of 110 l / cm and an ink load of 14mL / m² is used. First, a solid photosensitive resin plate is used for coating and printing. After a single printing, the ink is dried in an oven at 105℃ for 30 minutes. After multi-layer overprinting and curing, a base layer is obtained. Pure formic acid is drop-coated onto the surface of the base layer and air-dried at room temperature. Then, a patterned photosensitive resin plate is used for overprinting to form a patterned surface layer. After drying in an oven at 105℃ for 30 minutes, the patterned conductive polymer electrode layer 2 is finally prepared. Step 4: A 1mm thick encapsulation frame is attached circumferentially to the display portion of the patterned conductive polymer electrode layer 2 to form a square receiving cavity. The square receiving cavity contains a non-trigger area and a trigger space area. Step 5: Preparation of cellulose-based ion-conducting gel electrolyte: (1) Melt 1-allyl-3-methylimidazolium chloride at 85°C, and add 2% bamboo dissolving pulp, 8% dimethyl sulfoxide and 5% polyvinyl alcohol according to its mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a uniform transparent solution is formed. Cool down to 55°C, add 9% epichlorohydrin by mass of bamboo dissolving pulp, stir for 5 min, pour into a polytetrafluoroethylene mold, let stand at 4°C for 24 h to form, and then place in deionized water to regenerate to obtain the gel precursor. (2) Weigh acrylamide and dissolve it in deionized water at 10% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution for 24 hours to fully swell, and then perform in-situ polymerization at 40°C to obtain a composite gel. (3) Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 1.2 mol / L, and ethylene glycol accounts for 15% of the final solution volume. Soak the composite gel in the lithium perchlorate mixed solution for 24 hours to fully swell. After taking it out, wipe off the surface moisture to obtain cellulose-based ion-conductive gel electrolyte.

[0027] A cellulose-based ion-conducting gel electrolyte is attached to the surface of a patterned conductive polymer electrode layer 2, covering the non-trigger area and part of the trigger space area to form an ion-conducting layer 3. A metal foil with a thickness lower than the encapsulation border is covered on the surface of the patterned conductive polymer electrode layer 2, completely covering the trigger space area to form a metal thin film layer 4. A polyethylene terephthalate film is then covered on top of the ion-conducting layer 3 and the metal thin film layer 4 to form an encapsulation layer 5, ultimately forming a flexible self-driving information display device.

[0028] Example 4: A method for fabricating a self-driving information display device, comprising the following steps: Step 1: Select digital proofing paper as flexible substrate 1 for cutting, and remove surface dust and impurities through dust removal treatment; according to the design size, design solid blocks and photosensitive resin plates containing patterns; Step 2: First, wipe the surface of the polyethylene terephthalate film with dish soap, then use deionized water and anhydrous ethanol to ultrasonically clean the polyethylene terephthalate film for 5 minutes each, and finally blow it dry with nitrogen. Step 3: Prepare a conductive polymer ink with display properties for patterning the conductive polymer electrode layer 2: Take a poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add, in sequence, 4% dimethyl sulfoxide (DMSO), 8% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) relative to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 hours, and then sonicate for 30 minutes to disperse evenly; On a flexible substrate 1, conductive polymer inks with display properties are sequentially printed using a flexographic printing process. The squeegee angle is 60°, the squeegee loading pressure is 7N, the printing pressure is 100N, the printing speed is 0.2m / s, and an anilox roller with a line count of 110 l / cm and an ink loading of 14mL / m² is used. First, a solid photosensitive resin plate is used for coating and printing. After a single printing, the ink is dried in an oven at 105℃ for 30 minutes. After multi-layer overprinting and curing, a base layer is obtained. Pure formic acid is drop-coated onto the surface of the base layer and air-dried at room temperature. Then, a patterned photosensitive resin plate is used for overprinting to form a patterned surface layer. After drying in an oven at 105℃ for 30 minutes, the patterned conductive polymer electrode layer 2 is finally prepared. Step 4: A 0.6mm thick encapsulation frame is attached circumferentially to the display portion of the patterned conductive polymer electrode layer 2 to form a square receiving cavity. The square receiving cavity contains a non-trigger area and a trigger space area. Step 5: Preparation of cellulose-based ion-conducting gel electrolyte: (1) Melt 1-allyl-3-methylimidazolium chloride at 90°C, and add 1% bamboo dissolving pulp, 10% dimethyl sulfoxide and 4% polyvinyl alcohol according to its mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a homogeneous and transparent solution is formed. Cool down to 60°C, add epichlorohydrin at 8% of the mass of bamboo dissolving pulp, stir for 5 min, pour into a polytetrafluoroethylene mold, let stand at 4°C for 24 h to form, and then place in deionized water to regenerate to obtain the gel precursor. (2) Weigh acrylamide and dissolve it in deionized water at 7% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution for 24 hours to fully swell, and then perform in-situ polymerization at 50°C to obtain a composite gel. (3) Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 1 mol / L, and ethylene glycol accounts for 20% of the final solution volume. Soak the composite gel in the lithium perchlorate mixed solution for 24 hours to fully swell. After taking it out, wipe off the surface moisture to obtain cellulose-based ion-conductive gel electrolyte.

[0029] A cellulose-based ion-conducting gel electrolyte is attached to the surface of a patterned conductive polymer electrode layer 2, covering the non-trigger area and part of the trigger space area to form an ion-conducting layer 3. A metal foil with a thickness lower than the encapsulation border is covered on the surface of the patterned conductive polymer electrode layer 2, completely covering the trigger space area to form a metal thin film layer 4. A polyethylene terephthalate film is then covered on top of the ion-conducting layer 3 and the metal thin film layer 4 to form an encapsulation layer 5, ultimately forming a flexible self-driving information display device.

Claims

1. A method for preparing a cellulose-based ion-conducting gel electrolyte, characterized in that, Includes the following steps: S1. Melt 1-allyl-3-methylimidazolium chloride at 80-90℃, and add 1%~3% bamboo dissolving pulp, 8-12% dimethyl sulfoxide and 3-5% polyvinyl alcohol by mass. After the bamboo dissolving pulp and polyvinyl alcohol are completely dissolved, continue stirring until a homogeneous and transparent solution is formed. Cool down to 50-60℃, add 8-10% epichlorohydrin by mass of bamboo dissolving pulp and stir evenly. Pour into a polytetrafluoroethylene mold to form, and then place in deionized water for regeneration to obtain the gel precursor. S2. Weigh acrylamide and dissolve it in deionized water at 2%-10% of the total mass of the solution to prepare an acrylamide solution. Soak the gel precursor in the acrylamide solution until it swells completely, and then carry out in-situ polymerization at 40-70℃ to obtain a composite gel. S3. Dissolve anhydrous lithium perchlorate in a mixed solvent composed of ethylene glycol and deionized water. The concentration of lithium perchlorate in the resulting solution is 0.8-1.2 mol / L, and ethylene glycol accounts for 15-25% of the final solution volume. Immerse the composite gel in the lithium perchlorate mixed solution until it swells completely. After removing it, wipe off the surface moisture to obtain the cellulose-based ion-conductive gel electrolyte.

2. A self-driven information display device comprising the cellulose-based ion-conducting gel electrolyte as described in claim 1, characterized in that, The device comprises a flexible substrate (1), on which conductive polymer ink with display characteristics is sequentially printed by flexographic printing process. A base layer is formed by coating with a solid block photosensitive resin plate, and then a patterned surface layer is formed by overprinting with a patterned photosensitive resin plate. The two together constitute a patterned conductive polymer electrode layer (2). The patterned surface layer defines the active area that serves as the display part. A packaging frame is provided around the display part of the patterned conductive polymer electrode layer (2) to define a square cavity. A non-triggering area and a triggering space area are provided in the square cavity. The cellulose-based ion-conductive gel electrolyte is attached to the surface of the patterned conductive polymer electrode layer (2) and covers the non-triggering area and part of the triggering space area to form an ion-conducting layer (3). A metal foil is covered on the surface of the patterned conductive polymer electrode layer (2) and completely covers the triggering space area to form a metal thin film layer (4). A polyethylene terephthalate film is covered on top of the ion-conducting layer (3) and the metal thin film layer (4) to form a packaging layer (5), and finally a self-driven information display device is formed. When a trigger operation is applied to the position corresponding to the trigger space area on the top of the self-driven information display device, the encapsulation layer (5) undergoes local deformation, driving the metal thin film layer (4) downward to contact the patterned conductive polymer electrode layer (2), thereby forming an instantaneous conductive path in this area, and generating a self-generated potential inside the device. At this time, the metal thin film layer (4) serves as the electron supply end and establishes an electrical connection with the patterned conductive polymer electrode layer (2). Under the action of the ion conduction layer (3), ions undergo directional migration inside the device and participate in the reversible oxidation-reduction reaction at the electrode interface, causing the patterned conductive polymer electrode layer (2) to undergo an oxidation-reduction reaction, thereby causing a change in the visual color and realizing the rapid display of patterned information.

3. The self-driving information display device according to claim 2, characterized in that, The preparation process of the conductive polymer ink with display properties is as follows: Take poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS) aqueous dispersion, and add 3% to 5% dimethyl sulfoxide (DMSO), 3% to 10% polyvinyl alcohol (PVA), 4% isopropanol (IPA), and 1% Triton (TX-100) according to the mass of the PEDOT:PSS aqueous dispersion; stir at room temperature for 3 hours, and then sonicate for 30 minutes to disperse evenly.

4. A method for manufacturing a self-driving information display device as described in any one of claims 2-3, characterized in that, Includes the following steps: Step 1: Cut the flexible substrate (1) and remove surface dust and impurities through dust removal treatment; Based on the design dimensions, design solid blocks and photosensitive resin plates containing patterns; Step 2: Perform ultrasonic cleaning on the polyethylene terephthalate film; Step 3: Prepare conductive polymer ink with display properties for patterned conductive polymer electrode layer (2). On flexible substrate (1), use flexographic printing process to print conductive polymer ink with display properties sequentially. First, use solid photosensitive resin plate for coating printing. After single printing and drying, multi-layer overprinting and curing are performed to obtain the base layer. Pure formic acid is drop-coated on the surface of the base layer and air-dried at room temperature. Then, use patterned photosensitive resin plate to overprint to form a patterned surface layer. After drying, the patterned conductive polymer electrode layer (2) is finally prepared. Step 4: A 0.5-1mm thick encapsulation frame is attached circumferentially to the display portion of the patterned conductive polymer electrode layer (2) to form a square receiving cavity, in which a non-trigger area and a trigger space area are provided; Step 5: The prepared cellulose-based ion-conducting gel electrolyte is attached to the surface of the patterned conductive polymer electrode layer (2) and covers the non-trigger area and part of the trigger space area to form an ion-conducting layer (3); a metal foil with a thickness lower than the encapsulation frame is covered on the surface of the patterned conductive polymer electrode layer (2) and completely covers the trigger space area to form a metal thin film layer (4); a polyethylene terephthalate film is covered on the ion-conducting layer (3) and the metal thin film layer (4) to form an encapsulation layer (5), and finally a self-driven information display device is formed.

5. The method for preparing a self-driving information display device according to claim 4, characterized in that, The flexible substrate (1) mentioned in step 1 is digital proofing paper, and the metal foil is zinc foil, aluminum foil or iron foil with a thickness of 0.1~0.5mm.

6. The method for preparing a self-driving information display device according to claim 4, characterized in that, The ultrasonic cleaning process described in step 2 is as follows: First, wipe the surface of the polyethylene terephthalate film with detergent, then use deionized water and anhydrous ethanol to ultrasonically clean the polyethylene terephthalate film for 5 minutes each, and finally blow it dry with nitrogen.

7. The method for preparing a self-driving information display device according to claim 4, characterized in that, The flexographic printing described in step 3 uses the following process parameters: the squeegee angle is fixed at 60°, the squeegee loading pressure is 6-7N, the printing pressure is 100-250N, the printing speed is 0.2m / s-0.6m / s, and an anilox roller with a line count of 110l / cm and an ink load of 14mL / m² is used.

8. The method for preparing a self-driving information display device according to claim 4, characterized in that, The drying process described in step 3 involves placing the food in a 105°C oven and drying it at a constant temperature for 30 minutes.